1994
DOI: 10.1063/1.46380
|View full text |Cite
|
Sign up to set email alerts
|

Free-surface light emission from shocked Teflon

Abstract: Shock initiated light emission experiments were performed on Teflon shock loaded to pressures up to ~17 GPa. Radiances up to 600 x 106W 9 m-2/(ster 9 rim), were measured over a range of 390 to 820 nm. We have measured the spectra of light emitted upon reflection of the shock at the free surface and observed it to be distinctly non-thermal in nature. The light emission appears to result from bond destruction such as observed in shock recovery experiments on Teflon and in quasistatic experiments conducted on oth… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2007
2007
2016
2016

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(4 citation statements)
references
References 10 publications
(13 reference statements)
0
4
0
Order By: Relevance
“…The occurrence of the ultraviolet component in the emission spectrum can be due to the nonequilibrium emission from the contact zone or to a considerable excess of the hot spot temperature over the average PTFE temperature, which is ≈3000 K at a pressure of 51 GPa [16]. In [8], the emission spectrum of shock-compressed Teflon at ≈17 GPa was fitted to the black-body emission law at 5875 K. When the emission from the contact interface was eliminated by filling the gap with immersion oil, the effect of the advance of the electrical conductivity wave relative to the shock front was not observed. In this case, the light signal pulse increased exponentially (see curve 1 in Fig.…”
Section: Time Correlation Between Emission Signals and The Occurrencementioning
confidence: 99%
See 3 more Smart Citations
“…The occurrence of the ultraviolet component in the emission spectrum can be due to the nonequilibrium emission from the contact zone or to a considerable excess of the hot spot temperature over the average PTFE temperature, which is ≈3000 K at a pressure of 51 GPa [16]. In [8], the emission spectrum of shock-compressed Teflon at ≈17 GPa was fitted to the black-body emission law at 5875 K. When the emission from the contact interface was eliminated by filling the gap with immersion oil, the effect of the advance of the electrical conductivity wave relative to the shock front was not observed. In this case, the light signal pulse increased exponentially (see curve 1 in Fig.…”
Section: Time Correlation Between Emission Signals and The Occurrencementioning
confidence: 99%
“…The recorded spectra of shockinduced emission also differ from the black-or graybody emission spectrum. In particular, for Teflon, this has been shown experimentally by spectrometric studies [8]. An analysis of shock-induced emission profiles of crystalline NaCl samples [4] and water [5] has shown that the emission is due to the two possible locations of the sources: at the plate-sample interface and in the 1 volume of the material behind the shock.…”
Section: Introductionmentioning
confidence: 94%
See 2 more Smart Citations